Communication method of shared-port and shared-network in substation - Wei WANG (Dianxin kexue)
To realize shared-port and shared-network in substation,a method based on VLAN and the time division multiplexing technology were studied,and the wavelength mapping method based on WDM technology by mapping different services to different wavelengths was put forward.Finally,a method based on optical switch was put forward which realized the “shared-port and shared-network”by edge pre-processing equipment and optical switching equipment.